Tunable and Passively Mode-Locking Nd0.01:Gd0.89La0.1NbO4 Picosecond Laser - Shande Liu; Yuqing Zhao; Ke Zhang; Bo Chen; Ning Zhang; Dehua Li; Huiyun Zhang; Yuping Zhang; Lihua Wang; Shoujun Ding; Qingli Zhang (Molecules, 2021)
A high-quality Nd0.01:Gd0.89La0.1NbO4 (Nd:GLNO) crystal is grown by the Czochralski method, demonstrating wide absorption and fluorescence spectra and advantage for producing ultrafast laser pulses. In this paper, the tunable and passively mode-locking Nd:GLNO lasers are characterized for the first time. The tuning coverage is 34.87 nm ranging from 1058.05 to 1092.92 nm with a maximum output power of 4.6 W at 1065.29 nm. A stable continuous-wave (CW) passively mode-locking Nd:GLNO laser is achieved at 1065.26 nm, delivering a pulse width of 9.1 ps and a maximum CW mode-locking output power of 0.27 W.